Workshop Sistem Informasi Desa dan Kawasan (SiDeKa) Desa Pantae KecamataN Biboki Selatan - kelen, yoseph pius kuniawan; Sikas, Oktovianus; Manek, Siprianus (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
Law No. 14 of 2008 concerning Freedom of Public Information mandates that Public bodies must develop and develop information and documentation systems to manage Public Information properly and efficiently so that it can be easily accessed. This service aims to train village officials to use SiDeKa as one of the media that can encourage the emergence of four (4) types of novelty, namely: awareness, skills, habits and governance of Village Information Systems. These community service activities are carried out in three stages. The first stage is the location survey and distribution of ICT understanding questionnaires at the village / kelurahan level on Friday, 17 May 2019 at 09.00 - 11.00 WITA. The second phase is the SiDeKa workshop for Pantae village officials on Friday, June 28, 2019 from 08.00 - 13.00 WITA and the third stage is the distribution of feedback questionnaire on the implementation of SiDeKa activities that have been carried out on Friday, July 12, 2019 at 09.00 - 11.00 WITA. Constraints encountered include the lack of computer and internet facilities at the village office and there are still many village officials who do not yet have the knowledge in using information and communication technology devices. The benefit of this training activity is to increase the ability of Pantae village officials to manage coordinated village data with the help of a computer-based system so that they can provide accurate information and services that are more satisfying to the community.